Carbohydrate metabolism parameters in angina patients treated with metoprolol and its combination with trimetazidine - E. V. Bochkareva; O. V. Aleksandrovich; P. Yu. Bardybakhin; E. K. Butina; N. G. Kucheryavaya; I. N. Ozerova; V. A. Metelskaya (Кардиоваскулярная терапия и профилактика)
Aim. To study the effects of a β-adrenoblocker (β-AB) metoprolol (Mp) and its combination with trimetazidine (Tmd) on glucose tolerance and insulin sensitivity in patients with angina pectoris. Material and methods. In total, 28 men aged 46-68 years, with Functional Class (FC) II-III stable angina, positive exercise stress test (EST), and no prior β-AB therapy were examined. Individual Mp doses were selected based on the paired EST results. For one month, the Mp dose of 50 or 100 mg/d was administered twice a day; for the next month, participants received Mp and Tmd (70 mg/d). A standard glucose tolerance test (GTT) was performed at baseline and at the end of one-month periods of Mp or Mp + Tmd treatment. Carbohydrate metabolism disturbances were diagnosed according to the WHO criteria (1999). Insulin resistance (IR) was assessed by HOMA2-IR parameter, and tissue insulin sensitivity by ISI0,120 parameter. Results. After one month of Mp treatment, a decrease in fasting glucose levels was observed (p=0,025). At the same time, the GTT results demonstrated increased glucose levels 2 hours after glucose load, compared to baseline (p=0,049). Tissue insulin sensitivity (ISI0,120) showed some reduction (p=0,14), while the number of patients with impaired glucose tolerance (IGT) increased from 4 to 8 (p=0,006). The levels of fasting and post-load glycemia after one month of the combination therapy with Mp and Tmd were similar to those after the Mp treatment. Insulin levels at 2 hours after glucose load were higher than those observed after the Mp therapy (p=0,045). Compared to baseline, HOMA2-IR values increased, and IDI0,120 values decreased (p=0,036). The IDI0,120 dynamics suggested a reduction in insulin sensitivity for both treatment regimens. IGT was registered in 10 patients. Conclusion. In angina patients, impaired glucose control was observed as early as 1 month after the start of Mp treatment. This early impairment could be diagnosed by GTT. Although the combination therapy with Mp and Tmd did not prevent this impairment, but provided a greater antiischemic effect and, therefore, was clinically appropriate